Case Study Comparison: Limitations in Telehealth Relating to Poverty and Family Support - Jorgensen, Lindsey E.; Barrett, Rachel E. (Seminars in Hearing, 2021)
Telehealth appointments have grown in popularity due to the COVID-19 global pandemic. Three cases presented in this article show several different perspectives where telehealth was utilized. For the first patient, appointments were successfully completed via telehealth; however, the patient's family opted to continue with an unsecure internet connection at a local laundromat. For the second patient, a stable internet connection could not be obtained in his home, thus making telehealth appointments unavailable. The caregiver of this patient ended up driving to the clinic to have adjustments made in person. For the third patient, telehealth appointments were unavailable due to unstable internet connections as well as difficulty setting up video interpreting services. These cases highlight the idea that telehealth can be incredibly beneficial, when used correctly. For some, the option to attend appointments virtually gives them access to specialists that otherwise may not be available. For other patients, aspects such as access to smart devices and steady internet access must be considered to ensure a successful connection. The hope is that this article sheds light on some of the potential setbacks that can come from the use of telehealth appointments in a practice and provides discussion regarding for whom telehealth may be appropriate, even in pediatric patients. After reading this article, readers should be able to discuss ways in which there could be solutions for these barriers that may prevent some patients from utilizing these types of virtual appointments.
Keywords: telehealth; pediatric; barriers to healthcare; socioeconomics